2020
DOI: 10.1002/ijc.33302
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mammographic microcalcifications

Abstract: We examined the association between established risk factors for breast cancer and microcalcification clusters and their asymmetry. A cohort study of 53 273 Swedish women aged 30 to 80 years, with comprehensive information on breast cancer risk factors and mammograms, was conducted. Total number of microcalcification clusters and the average mammographic density area were measured using a Computer Aided Detection system and the STRATUS method, respectively. A polygenic risk score for breast cancer, including 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(100 reference statements)
0
7
1
Order By: Relevance
“…Furthermore, we failed to observe the inverse association of vitamin D and calcium intake with breast density in premenopausal women as reported in several observational studies 19,20 . Nonetheless, we observed that higher vitamin D and calcium intakes were associated with lower breast density in women without microcalcifications, a group that tend to be younger than women with microcalcifications 31 . However, these inconstancies may partly be explained by the study population.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Furthermore, we failed to observe the inverse association of vitamin D and calcium intake with breast density in premenopausal women as reported in several observational studies 19,20 . Nonetheless, we observed that higher vitamin D and calcium intakes were associated with lower breast density in women without microcalcifications, a group that tend to be younger than women with microcalcifications 31 . However, these inconstancies may partly be explained by the study population.…”
Section: Discussioncontrasting
confidence: 64%
“…As it remains unclear if the presence of microcalcifications is a risk factor or a marker of breast cancer progression, and knowing that the presence of microcalcification clusters was recently associated with high breast density, 31 we assessed the association of daily vitamin D and calcium intakes with age-related lobular involution and breast density adjusting for and stratifying for microcalcification status.…”
Section: Methodsmentioning
confidence: 99%
“…These results are novel but not surprising, given that these risk models directly or indirectly take mammographic features into account. Specifically, the KARMA model 27 directly incorporates breast density, masses, microcalcifications, and their asymmetries; the Tyrer-Cuzick model 21 incorporates hormone-related factors, which can affect mammographic features 28,29 ; and the polygenic risk model positively correlates with not only mammographic density but also microcalcifications and masses. 30 However, when restricting our analyses to women who were recalled, we found that model estimated risks were associated with higher risk of having true-positive than false-positive recalls.…”
Section: Discussionmentioning
confidence: 99%
“…The full model was adjusted for age, smoking status, BMI, lipid-lowering medication, hypertension, physical activity, alcohol consumption, education, age at first birth, menopausal status, HRT use, and oral contraception use. Since a BC diagnosis and subsequent treatment may be a significant competing risk for cardiometabolic mortality, we also performed competing risk analyses with the crr function from the cmprsk package 20 in R. Finally, the age-adjusted mortality rate and confidence intervals per 1000 person-years was computed with ageadjust.direct function implemented in the library epitools in R. 49…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, higher body mass index (BMI), current smoking behaviour as well as moderate to high alcohol consumption resulted in fewer MC. 20 Importantly, multiple reports indicated that mammographic MC are associated with increased prevalence and incidence of cardiovascular and coronary artery disease (summarized in 21 ). Similarly, a higher number of MC are frequently observed in women with chronic renal failure, 22 , 23 thus strongly implicating MC to be involved in multiple cardiometabolic diseases.…”
Section: Introductionmentioning
confidence: 99%